Distribution and Risk Factors of Water-Related Accidents for General Aviation Aircraft - Ruiliang Yang; LibinYang; Lina Zhao; Donghan Geng (International Journal of Aerospace Engineering)
In the past two decades, dozens to more than a hundred people have died each year in water-related accidents, most of which general aviation has accounted for. To identify the distribution and risk factors of fatal water-related accidents for general aviation aircraft, a total of 594 water-related accidents according to 14 CFR Part 91 from 2009 to 2019 were chosen from the National Transportation Safety Board’s online database. A two-step approach, consisting of a univariable logistic regression and a multivariable logistic regression, was performed to estimate the effects of 28 parameters. Results show that aircraft with a rated power of more than 100 horsepower (odds ratio>5), instrument conditions (odds ratio=25.585), flying night operations (odds ratio=3.717), and cruise phase (odds ratio=11.699) possessed an elevated risk for a fatal outcome. This research is the first to identify the distribution and risk factors of fatal water-related accidents under 14 CFR Part 91. The necessity and importance of survival equipment for water-related accidents are also highlighted in this paper.